The warrior's heart : becoming a man of compassion and courage - Greitens, Eric, 1974- (Houghton Mifflin Harcourt, 2012)
Eric Greitens shares his life journey from being an average kid to working to make a difference in the world's trouble spots and joining the Navy SEALS to protect the weak, and encourages readers to reflect on the power of choice and acts of courage.